(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2015)
In Italy the deep crisis of the judicial system, and in particular of the jail system, has allowed the development of an intense deinstitutionalization. A new Italian law (81/2014) recently established dismission of all Psychiatric Forensic Hospitals and the transferring of old and new “forensic” patients to the Rems (Residence for the implementation of security measures) or local Mental Health Department, at time in many instances in the same common settings of acute psychiatric services, community and territorial psychiatry mixed with “common” psychiatric patients. This change already introduced several problems, also legal, with strong preoccupation among operators, other patients and public opinion as concerns both treatment efficiency and safety of the cure.